Integrating global citizenship and transformative learning: An explanatory sequential analysis of graduate school curricula - Dalisay, Joanne; Bladera, Philip; Eusebio, Ellaine Joy; Fontamillas, Kreisler; Patiam, Aljay Marc (Journal of Interdisciplinary Studies in Education, 2026)
This study investigates the integration of Global Citizenship Education (GCED) and Transformative Learning Theory (TLT) within the graduate curricula of Romblon State University. Using a sequential explanatory mixed-methods design, the research analyzed survey data from 88 graduate students through descriptive and inferential statistics, followed by qualitative interviews and focus group discussions with students, faculty, and administrators. Results indicate that key transformative learning processes—critical reflection, rational discourse, experiential learning, and perspective transformation—are substantially embedded in the curriculum. These processes contribute to the development of global awareness, social justice orientation, cultural competence, civic engagement, and ethical responsibility among graduate students.